Temperature Compensation for Transformer-type Transducer - Kanoknuch Songsuwankit; Vanchai Riewruja; Pakorn Watanachaturaporn; Apinai Rerkratn; Wandee Petchmaneelumka (My University, 2021)
A novel technique to compensate the temperature effect of a transformer-type transducer is proposed in this paper.The effect of the ambient temperature on the transformer-type transducer is investigated from a primary-winding current.The advantage of the proposed technique is that the temperature effect is compensated without requiring a temperature sensor, making it suitable for applications in robotic and automation systems operated in harsh environments.The primary-winding current of the transducer is generated using a second-generation current conveyor (CCII).The excitation signal of the transformer-type transducer is driven by the CCII and the current flowing through the primary winding is transferred to an output signal of the CCII.The deviation of the primary-winding current due to the temperature effect is evaluated from the output signal of the CCII.The temperature effect on the transducer is manipulated by a closed-loop principle using a subtract-and-sum action instead of a traditional proportional-plusintegral action to eliminate the deviation of the primary-winding current.Therefore, the temperature effect on the transducer is compensated.A linear variable differential transformer (LVDT) is used to demonstrate the proposed technique, whose performance is discussed in detail and confirmed experimentally.All devices used in this experiment are commercially available.Experimental results show that the measured error of the output signal from the LVDT at 70 °C can be reduced from 6.2% without temperature compensation to 0.06% by using the proposed technique, which has the advantages of a low cost, simple configuration, and high performance.
Keywords: Sensor Technology and Measurement Systems